2014
DOI: 10.1186/s12933-014-0136-5
|View full text |Cite
|
Sign up to set email alerts
|

Visceral adiposity index and risks of cardiovascular events and mortality in prevalent hemodialysis patients

Abstract: BackgroundThe visceral adiposity index (VAI) is a newly-derived measure of visceral adiposity with well-validated predictive power for cardiovascular (CV) outcomes in the general population. However, this predictability has not been investigated in hemodialysis patients, and whether VAI is superior to waist circumference (WC) and waist-to-height ratio (WHtR) in predicting CV outcomes and survival in hemodialysis patients remains unknown.MethodsWe performed a prospective study including 464 prevalent hemodialys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 40 publications
(70 reference statements)
2
22
0
Order By: Relevance
“…In our multivariate and Cox regression results, VAI predicted a higher risk of composite outcomes, CV outcomes and mortality. Similar results were reported in former studies [36].…”
Section: Discussionsupporting
confidence: 93%
“…In our multivariate and Cox regression results, VAI predicted a higher risk of composite outcomes, CV outcomes and mortality. Similar results were reported in former studies [36].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the VAI, several studies have demonstrated its usefulness in measuring of visceral fat [23,30], prediction of metabolic syndrome [31] and arterial stiffness [32], and as risk marker to cardiometabolic diseases [25,30,3335,36]. Elisha et al [37], analyzing 99 overweight women in the postmenopausal period, observed that the VAI was a weak predictor to change of visceral fat percentage after a weight loss program for six months.…”
Section: Discussionmentioning
confidence: 99%
“…VAI is a marker of visceral adipose dysfunction and is strongly associated with cardiovascular events and type 2 diabetes (12,30,31). VAI is significantly correlated with inflammation and insulin resistance in patients with type 2 diabetes and cardiovascular disorders (12,32).…”
Section: Vai and Tg/hdl Ratio In Hypogonadismmentioning
confidence: 99%